The Relationship Between Inflation and Consumer Confidence: An Analysis in The Case of Turkey (Third Sector Social Economic Review, 2025)
Policymakers must base their macroeconomic analyses on consumer behavior when formulating economic policies. The consumer confidence index, which reflects individuals' future expectations, general economic outlook, and financial situation, has a complex relationship with inflation, which can develop both causally and simultaneously, and plays a significant role in determining demand-side movements. This study investigates the causal relationship between the consumer price index and the consumer confidence index in Turkiye using monthly data for the period 2012:12-2025:06. It analyzes the direction and dynamics of this relationship from a long-term and short-term perspective using econometric methods. The study finds a significant, bidirectional, negative relationship between the consumer confidence index variable and inflation in Turkiye. The study finds that a 1% increase in consumer confidence leads to a 7.26-point decrease in inflation in the long term, while a 1-point increase in inflation reduces consumer confidence by 5.7%. In addition, the comparative effect sizes obtained show that the effect of inflation on consumer confidence (5.7%) and the effect of consumer confidence on inflation (5.5%) are very similar in intensity, demonstrating more clearly and methodologically stronger that the relationship operates in a reciprocal and balanced structure. While the two variables move in equilibrium, the confidence-inflation relationship interacts and plays a significant role in economic policy design. This study emphasizes the importance of considering consumer expectations and confidence in achieving price stability.
Keywords: ARDL; Inflation; Consumer Confidence Index; Turkiye